Prerequisites for Emergency Laparoscopic Surgery for Colorectal Cancer - Wan Kim Young (Journal of Surgery Proceedings, 2016)
This practical overview lists prerequisites for emergent laparoscopic colorectal cancer surgery, including team readiness, equipment, and perioperative protocols to optimize patient safety.
Keywords: Emergencies